Assessment of chlorophyll and water quality using remote sensing and GIS imagery in the Cauvery watershed of Karnataka, India - Karunakaran, D.; Sahu, S. K.; Pandit, Arun; Sharma, A. P. (Indian Journal of Fisheries, 2019)
India has vast inland water resources having immense potential for aquaculture potential. Assessment of water quality parameters is a pre-requisite to any scientific intervention as they are of prime importance in fisheries perspective. However, monitoring water quality parameters of such vast area is not an easy task with the conventional tools and methods. In the present study, water quality parameters and chlorophyll pigment concentration were assessed using IRS P-6 remote sensing imagery in the Cauvery watershed of Karnataka State, India. Images captured by optical satellite sensors are often obscured by atmospheric effects. Hence, the images were rectified by Dark pixel subtraction method before analysing data in order to extract useful information from the imagery. The study revealed that there was significant correlation between spectral reflectance and in-situ water quality parameters. Near infra-red band (0.77-0.86 µm), was useful to assess the water quality parameters like depth, specific conductivity, total alkalinity, chlorinity, salinity and turbidity. Similarly, short wave infrared band (1.55-1.70 µm) was useful for assessing chlorophyll-a. However, the models were found to be region specific and they appear to have potential for monitoring water quality of large water bodies at regular intervals.Keywords:  Chlorophyll a, Cauvery watershed,  IRS P-6, Remote Sensing, Water quality